Study on Significance of Physical Activity on Public Health: Exploring the Impact of Physical Activity on Public Health (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Human beings are born to be physically active. Being physically active gives several advantages and is essential for a healthy life. Physical inactivity is to date one of the major risk factors for developing non-communicable diseases, which are responsible for nearly 70 of all deaths. It is well documented in the literature that daily physical activity reduces the risk of non-communicable diseases. The level of physical activity differs between regions of the world and between the countries. Moreover, there are age and gender differences.